The effect of acute sleep deprivation on skeletal muscle protein synthesis and the hormonal environment - Lamon, Séverine; Morabito, Aimee; Arentson‐Lantz, Emily; Knowles, Olivia; Vincent, Grace Elizabeth; Condo, Dominique; Alexander, Sarah Elizabeth; Garnham, Andrew; Paddon‐Jones, Douglas; Aisbett, Brad (Physiological reports, 2021)
Chronic sleep loss is a potent catabolic stressor, increasing the risk of metabolic dysfunction and loss of muscle mass and function. To provide mechanistic insight into these clinical outcomes, we sought to determine if acute sleep deprivation blunts skeletal muscle protein synthesis and promotes a catabolic environment. Healthy young adults (N = 13; seven male, six female) were subjected to one night of total sleep deprivation (DEP) and normal sleep (CON) in a randomized cross‐over design. Anabolic and catabolic hormonal profiles were assessed across the following day. Postprandial muscle protein fractional synthesis rate (FSR) was assessed between 13:00 and 15:00 and gene markers of muscle protein degradation were assessed at 13:00. Acute sleep deprivation reduced muscle protein synthesis by 18% (CON: 0.072 ± 0.015% vs. DEP: 0.059 ± 0.014%·h‐1, p = .040). In addition, sleep deprivation increased plasma cortisol by 21% (p = .030) and decreased plasma testosterone by 24% (p = .029). No difference was found in the markers of protein degradation. A single night of total sleep deprivation is sufficient to induce anabolic resistance and a procatabolic environment. These acute changes may represent mechanistic precursors driving the metabolic dysfunction and body composition changes associated with chronic sleep deprivation. Acute sleep deprivation decreases muscle protein synthesis in young, healthy males and females. Acute sleep deprivation promotes a catabolic hormonal environment. Future research should investigate sex‐specific differences.